KEBIJAKAN FORMULASI PIDANA MATI DALAM PEMBARUAN KITAB UNDANG-UNDANG HUKUM PIDANA NASIONAL - B. FARHANA KURNIA LESTARI; JAUHARI D. KUSUMA; JURWAEIS MARJA SEKA (Universitas Mahasaraswati K. Mataram, 2024)
This study aims to determine the comparison of death penalty sanctions in the 2023 Criminal Code Update and the old Criminal Code that is still in force today and also to determine the legal certainty of death penalty legal certainty in the National Criminal Code Update. The research method used in this study is a normative legal research method which is legal research conducted using a statutory approach and and analysis of legal concepts by analyzing criminal and penal concepts and applicable laws and regulations in Indonesia related to this research.From the results of the study, that the comparison of death penalty sanctions in the renewal of the old Criminal Code and the new Criminal Code, namely the old Criminal Code, the death penalty is regulated in article 10 which explains that the death penalty is the main crime and is the highest criminal sanction. Meanwhile, in the new Criminal Code, the death penalty is no longer included in the main crime and changes to an alternative crime with the provision of probation for 10 (sepulu) years. If the death row prisoner shows commendable attitudes and actions, the death penalty can be changed to life imprisonment by Presidential Decree after obtaining the consideration of the Supreme Court. Legal certainty The renewal of the death penalty in Indonesian criminal law can be achieved by referring to Indonesian laws and regulations governing the death penalty. In the new Criminal Code, provisions on the death penalty are regulated in article 98, article 99, article 100 paragraph (1), paragraph (2), paragraph (3), paragraph (4), article 101 and article 102. This article regulates the formulation of the death penalty in the Criminal Code Reform which is threatened alternatively as a last resort to prevent the commission of criminal acts and protect the community.